Incorporation size of lymph node metastasis focus and pre-ablation stimulated Tg could more effectively predict clinical outcomes in differentiated thyroid cancer patients without distant metastases - Xie, Jiahao; Chen, Pan; Wang, Jing; Luo, Xiaoqin; Luo, Jiaxin; Xiong, Xiaoli; Li, Chunyan; Pan, Liqin; Wu, Juqing; Feng, Huijuan; Ouyang, Wei (Frontiers in Endocrinology, 2023)
Background: The size of lymph node metastasis (LNM) and pre-ablation stimulated Tg (ps-Tg) were key predictors of clinical prognosis in differentiated thyroid cancer (DTC) patients, however, very few studies combine the above two as predictors of clinical prognosis of DTC patients. Methods: Persistent/recurrent disease and clinicopathologic factors were analyzed in 543 DTC patients without distant metastases who underwent LN dissection, near-total/total thyroidectomy, and radioiodine ablation. Results: In the multivariate analysis, size of LNM, ps-Tg, and the activity of 131I significantly correlated with long-term remission. The optimal cutoff size of LNM 0.4 cm-1.4 cm (intermediate-risk patients) and >1.4cm (high-risk patients) increased the recurrence risk (hazard ratio [95% CI], 4.674 [2.881-7.583] and 13.653 [8.135–22.913], respectively). Integration of ps-Tg into the reclassification risk stratification showed that ps-Tg ≤ 10.0 ng/mL was relevant to a greatly heightened possibility of long-term remission (92.2%–95.4% in low-risk patients, 67.3%–87.0% in intermediate-risk patients, and 32.3%–57.7% in high-risk patients). Conclusion: The cutoff of 0.4 cm and 1.4 cm for a definition of size of LNM in DTC patients without distant metastases can reclassify risk assessment, and incorporating ps-Tg could more effectively predict clinical outcomes and modify the postoperative management plan.